6n(n-1)+4=36

Simple and best practice solution for 6n(n-1)+4=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n(n-1)+4=36 equation:



6n(n-1)+4=36
We move all terms to the left:
6n(n-1)+4-(36)=0
We add all the numbers together, and all the variables
6n(n-1)-32=0
We multiply parentheses
6n^2-6n-32=0
a = 6; b = -6; c = -32;
Δ = b2-4ac
Δ = -62-4·6·(-32)
Δ = 804
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{804}=\sqrt{4*201}=\sqrt{4}*\sqrt{201}=2\sqrt{201}$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-2\sqrt{201}}{2*6}=\frac{6-2\sqrt{201}}{12} $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+2\sqrt{201}}{2*6}=\frac{6+2\sqrt{201}}{12} $

See similar equations:

| -3t=-1.2 | | -(8p-8)+3=7p+18 | | -3(w+2=2(w+6)+7 | | -1=-4(9-x)+3-2)=-290 | | 5(k-7=7 | | a÷5=52 | | 210d=9 | | x/45=90= | | 12(x+9)=7x-5 | | 5(y–2)−2=2(y+1)−5 | | (2y+17)+7(15)+18=180 | | 6x+44x+6=90 | | 12n-6(1-12n)=3(12n-2) | | 6x+33+3x+30=180 | | 5.3(x-5)=2.94+3.7 | | c=51(18)+4.4 | | 3a-5=37 | | 7x+21=5x+49 | | 5/12=3.5/x | | 6-2x=6x10x+16 | | 2x+21=5x+49 | | (6+8)2=-9x5 | | 12/5=x/3.5 | | 1/29(x)=6 | | 2(3x+1)+3(x-7)=265 | | 3x-9+x+x=180 | | -3x+22=-20 | | -32=2d | | 13=-7x-29 | | -5x=2x-2 | | 2x-3(x-3)=8 | | (7y+18)+(2y+17)=180 |

Equations solver categories